Sertularia marginata (Cnidaria: Hydrozoa) in the Mediterranean: an alien species in expansion? - GONZÁLEZ-DUARTE, M. M.; MEGINA, C.; BETHENCOURT, M. (Mediterranean Marine Science, 2013)
Mature and dense populations of the tropical hydroid species Sertulariamarginata were detected in the Alboran Sea (Western Mediterranean) and in the Atlantic coast of the Strait of Gibraltar. Until now, it had only been recorded in the eastern basin within the Mediterranean Sea.This species has previously been recorded in estuaries and anthropogenichabitats but, in the area studied here, we only found it in natural zones. These observations could indicate an early expansion and naturalization in the Mediterranean Sea. Due to its limited dispersion capacity by its own natural means and the history of its records, the observations provided here support the hypothesis of an arrival and a spread by anthropogenic vectors.A pathway of arrival and dispersion of alien species into the Mediterranean Sea is proposed for future monitoring: from Macaronesia (particularly Canary Islands) to the Atlantic coast of the Strait of Gibraltar and from here into the Mediterranean.